Manajemen Pengembangan Desain Berbasis Pendidikan Transformatif dalam Meningkatkan Kompetensi Akademik Mahasiswa PAI - Nurlaila Ana; Ahmad Ta’rifin; Ulul Albab (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2026)
Despite growing attention to transformative education in higher education, there is limited empirical evidence on how to systematically integrate it into program design to strengthen students’ academic competence in Islamic higher education institutions. This study develops and validates a transformative education-based program design for the Islamic Religious Education Study Program at Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan. Employing a Research and Development approach based on the ADDIE model, the study collected data through interviews, questionnaires, observations, document analysis, and focus group discussions, and conducted expert validation with lecturers, students, curriculum specialists, and institutional stakeholders. The findings demonstrate that a systematic and transformative program design significantly enhances students’ academic competence by improving curriculum coherence, learning quality, student engagement, and attainment of competencies. Among the examined components, integrative program design emerged as the most influential factor in fostering cognitive, affective, and psychomotor learning outcomes. The development process produced validated program design documents, learning modules, lesson plans, and evaluation guidelines that achieved high feasibility and usability ratings from experts and practitioners. Pilot implementation across selected courses further confirmed the effectiveness of the developed model in promoting meaningful learning experiences and strengthening academic competencies. This study contributes a validated transformative education framework that integrates Islamic values with outcome-based learning principles, extending the discourse on curriculum innovation and offering a scalable model for curriculum reform and sustainable academic development in Islamic higher education.